2016
DOI: 10.1002/celc.201600343
|View full text |Cite
|
Sign up to set email alerts
|

Iodine as a Temperature‐Responsive Redox Shuttle Additive for Swelling Suppression of Lithium‐Ion Batteries at Elevated Temperatures

Abstract: The swelling issue by gas evolution at elevated temperatures (85–90 °C) is one of the major challenges related to current Li‐ion batteries (LIBs). We herein demonstrate that iodine (I2) as a redox shuttle additive, when its dose is properly determined, can suppress the swelling behavior of LiCoO2/graphite Al‐pouch cells during storage at 90 °C without sacrificing other cell performances. This approach is based on two findings: 1) swelling during 90 °C storage is severe only when the cells are fully charged, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
7
0
4
Order By: Relevance
“…[70][71][72] Furthermore,s urface modifications including fluorination treatments, [29,73] halide coatings, [74,75] and halide-reinforced chemical adsorption [76,77] were conducted to stabilize the electrode structure and electrode/electrolyte interfaces of intercalation electrodes and conversion electrodes,s uch as sulfur and metal oxides.E lectrode/electrolyte interface modifications could also be achieved by employing fluorinated solvents or electrolytes containing halogens. [7,[78][79][80][81] In addition, fluoropolymers generally have high chemical and electrochemical stabilities,a nd their porous and mechanical properties can be tuned by synthetic methods.I ndeed, some fluoropolymer-based separators have proven to be beneficial for enhancing battery performance.…”
Section: Halides In Lithium-ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…[70][71][72] Furthermore,s urface modifications including fluorination treatments, [29,73] halide coatings, [74,75] and halide-reinforced chemical adsorption [76,77] were conducted to stabilize the electrode structure and electrode/electrolyte interfaces of intercalation electrodes and conversion electrodes,s uch as sulfur and metal oxides.E lectrode/electrolyte interface modifications could also be achieved by employing fluorinated solvents or electrolytes containing halogens. [7,[78][79][80][81] In addition, fluoropolymers generally have high chemical and electrochemical stabilities,a nd their porous and mechanical properties can be tuned by synthetic methods.I ndeed, some fluoropolymer-based separators have proven to be beneficial for enhancing battery performance.…”
Section: Halides In Lithium-ion Batteriesmentioning
confidence: 99%
“…[147] Park et al demonstrated that the use of iodine as ar edox shuttle additive suppressed the swelling of the LiCoO 2 /graphite cell during storage at 90 8 8Cwithout the deterioration of other cell properties. [81] Boulineau et al prepared aseries of highly ionconductive Li 6 PS 5 X( X= Cl, Br,I )L i-argyrodites as solidstate electrolytes of LIBs. [148] Li 6 PS 5 Cl with optimized structures showed aconductivity of 1.33 10 À3 Scm À1 at 298 Kand ah igh electrochemical stability of up to 7V(versus Li + /Li).…”
Section: Electrolyte Design and Additivesmentioning
confidence: 99%
“…Die Anpassungen an die Elektroden/Elektrolyt-Grenzflächen kçnnen auch durch Einsatz von fluorierten Lçsungsmitteln oder Elektrolyten, die Halogene beinhalten, realisiert werden. [7,[78][79][80][81] Außerdem haben Fluorpolymere generell hohe chemische und elektrochemische Stabilitäten und ihre porçsen und mechanischen Eigenschaften kçnnen mit synthetischen Methoden angepasst werden. Einige auf Fluorpolymeren basierenden Separatoren erwiesen sich als vorteilhaft fürdie Steigerung der Batterieleistung.…”
Section: Halogenide In Lithium-ionen-batterienunclassified
“…[147] Park et al zeigten, dass die Verwendung von Iod als Redox-Shuttle-Additiv die Anschwellung der LiCoO 2 /Graphit-Zelle während der Speicherung bei 90 8 8Cverhinderte,und dabei ohne Verschlechterung anderer Zelleigenschaften. [81] Boulineau et al präparierten eine Reihe von Li 6 PS 5 X-Li-Argyroditen (X = Cl, Br, I) mit hoher Ionenleitfähigkeit als Elektrolyten im Festzustand von LIBs. [148] Das Li 6 PS 5 Cl wies mit optimierten Strukturen eine Leitfähigkeit von bei 298 Ka uf und eine hohe elektrochemische Stabilitätv on bis zu 7V (vs.L i + /Li).…”
Section: Elektrolytdesign Und Additiveunclassified
“…The fiber‐shaped lithium–air batteries demonstrated better thermal stability beyond many other kinds of batteries. For lithium‐ion batteries (LIBs), the highest working temperature has been increased to 90 °C by introducing additives to electrolyte, optimizing electrode material, using polymer electrolyte, or adding ionic liquids; for lithium–sulfur (Li–S) batteries, a general strategy was adopted by changing electrode materials, by which they could withstand a peak temperature of 70 °C. In the case of lithium–oxygen (Li–O 2 ) batteries, polymer electrolyte was employed to obtain a flexible battery and increased the working temperatures to 80 °C.…”
mentioning
confidence: 99%